Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

Tailored synthesis of ultra-stable Au@Pd nanoflowers with enhanced catalytic properties using cellulose nanocrystals - Hakkeem, Hasna M. Abdul; Babu, Aswathy; Shilpa, Nagaraju; Venugopal, Adithya A.; Mohamed, A. P.; Kurungot, Sreekumar; Pillai, Saju (Carbohydrate Polymers, 2022)
A green strategy for the synthesis of bimetallic core-shell Au@Pd nanoflowers (NFs) employing banana pseudostem-derived TEMPO-oxidized cellulose nanocrystals (TCNC) as both capping and shape-directing agent via seed-mediated method is presented. Flower-like nanostructures of Au@Pd bound to TEMPO-oxidized cellulose nanocrystals (TCNC-Au@Pd) were decorated on amino-functionalized graphene (NH2-RGO) without losing their unique structure, allowing them to be deployed as an efficient, reusable and a green alternative heterogeneous catalyst. The decisive role of TCNC in the structural metamorphosis of nanoparticle morphology were inferred from the structural and morphology analyses. According to our study, the presence of -OH rich TCNC appears to play a pivotal role in the structured evolution of intricate nanostructure morphology. The feasibility of the bio-supported catalyst has been investigated in two concurrently prevalent model catalytic reactions, namely the oxygen reduction reaction (ORR) and the reduction of 4-nitrophenol, the best model reactions in fuel cell and industrial catalytic applications, respectively.
Keywords: Au@Pd; catalysis; Cellulose nanocrystals; Nanoflowers; oxygen reduction reaction